Das Leib-Seele-Problem im Spannungsfeld von modaler Ontologie und inferentialistischer Sprachphilosophie (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
My considerations written to honour the 60th birthday of my philosopher-friend Danie Strauss start with a sketch of the body-mind-problem in modern philosophy. Secondly I discuss the theory of modal aspects with special reference to the uniqueness, diversity and coherence of modal aspects, and thirdly I apply this theoretical approach to the body-mindproblem in order to refute the reductionism of approaches alleging the identity of bodily and mental processes. After having shown at least one similarity between Strauss’s theory of modal aspects and the Aristotelian soul doctrine I dwell on a further possibility of resolving the famous bodymind-problem. According to Kant the concept of ›Ich‹ (›I‹) is differentiated in ›ICH‹ (›Me‹) and ›ich‹ (›I‹), and the ›ich‹ is defined as the subject of reason that can’t be conscious like the Me, but that is the force of getting the Me into consciousness. This differentiation is vindicated by Wittgenstein, and hence the neuro-physiological base of mental processes is no longer of interest, but the (cognitive, linguistic and social) practices (›Praxen‹) are in the core of philosophical consideration, because the ›ich‹ is embedded in them and embeds itself in them. From these considerations follows a change in metaphors: Not the ›inner‹ is important, but the (external) ›logical room of reasons‹ (formulated by Sellars and Brandom). Thus I finally claim: If the mentalistic and representational vocabulary of modern philosophy is constitutionally dependent on the perspective of the third person, then a new way of resolving the bodymind-problem is given with the praxelogical approach in philosophy.